Human dental pulp cells response to mineral trioxide aggregate (MTA) and MTA Plus: cytotoxicity and gene expression analysis - Rodrigues, E. M. [UNESP]; Cornélio, A. L.G. [UNESP]; Mestieri, L. B. [UNESP]; Fuentes, A. S.C.; Salles, L. P.; Rossa-Junior, C. [UNESP]; Faria, G. [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Tanomaru-Filho, M. [UNESP] (Wiley, 2017)
Aim: To investigate the cytotoxicity, osteogenic bioactivity and mRNA expression of osteogenic markers of bone morphogenetic protein 2 (BMP-2), osteocalcin (OC) and alkaline phosphatase (ALP) induced by the extracts of set MTA Plus (MTA P) (Avalon Biomed Inc. Bradenton, FL, USA) in comparison with MTA (Angelus, Londrina, PR, Brazil) on human dental pulp cells (hDPCs). Methodology: Cell viability was assessed by mitochondrial dehydrogenase enzymatic (MTT) assay, and the mechanism of cell death was evaluated by flow cytometry. Bioactivity was evaluated by alkaline phosphatase (ALP) assay and detection of calcium deposits with alizarin red staining (ARS). The gene expression of BMP-2, OC and ALP was quantified with real-time PCR. Statistical analysis was performed with analysis of variance and Bonferroni or Tukey post-test (α = 0.05). Results: MTA and MTA P were not cytotoxic and did not induce apoptosis. MTA P had significant higher ALP activity in relation to MTA and the control (P < 0.05). MTA had a significantly higher percentage of mineralized area than MTA P (P < 0.05). The expression of BMP2 and OC mRNA was significantly higher in cells exposed to MTA than MTA P after 1 day (P < 0.05). At day 3, the mRNA expression of ALP was significantly higher in MTA P compared with MTA (P < 0.05). Conclusions: MTA and MTA Plus were noncytotoxic, increased mineralization processes in vitro and induced the expression of osteogenic markers.
Keywords: cytotoxicity; dental pulp cells; mineral trioxide aggregate; MTA Angelus; MTA Plus; pulp capping